2023
DOI: 10.1002/chem.202300336
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Off‐Cycle and Deactivation Pathways in Radical‐Type Carbene Transfer Catalysis

Abstract: Transition metal radical‐type carbene transfer catalysis is a sustainable and atom‐efficient method to generate C−C bonds, especially to produce fine chemicals and pharmaceuticals. A significant amount of research has therefore been devoted to applying this methodology, which resulted in innovative routes toward otherwise synthetically challenging products and a detailed mechanistic understanding of the catalytic systems. Furthermore, combined experimental and theoretical efforts elucidated the reactivity of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It was found that with an excess of iodonium ylide, a biscarbene complex was formed that transferred the carbene moiety onto the double bond, forming cyclopropane with high yields and short reaction times (up to 99%, < 5 min). In this work, the general sensitivity of metal carbene radical complexes toward deactivation was also observed: most metal carbene radical complexes are very competent in abstracting a hydrogen from weak C–H bonds . Contrarily, the group of Che showed that the hydrogen atom transfer (HAT) reaction can actually be used to generate the desired active radical species, thereby leading to product formation rather than deactivation …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…It was found that with an excess of iodonium ylide, a biscarbene complex was formed that transferred the carbene moiety onto the double bond, forming cyclopropane with high yields and short reaction times (up to 99%, < 5 min). In this work, the general sensitivity of metal carbene radical complexes toward deactivation was also observed: most metal carbene radical complexes are very competent in abstracting a hydrogen from weak C–H bonds . Contrarily, the group of Che showed that the hydrogen atom transfer (HAT) reaction can actually be used to generate the desired active radical species, thereby leading to product formation rather than deactivation …”
Section: Introductionmentioning
confidence: 83%
“…In this work, the general sensitivity of metal carbene radical complexes toward deactivation was also observed: most metal carbene radical complexes are very competent in abstracting a hydrogen from weak C−H bonds. 20 Contrarily, the group of Che showed that the hydrogen atom transfer (HAT) reaction can actually be used to generate the desired active radical species, thereby leading to product formation rather than deactivation. 21 However, all of the above-mentioned reactions require highenergy carbene precursors bearing excellent leaving groups to generate the reactive carbene radical intermediate (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this work, the general sensitivity of metal carbene radical complexes toward deactivation was also observed: most metal carbene radical complexes are very competent in abstracting a hydrogen from weak C-H bonds. 20 Contrarily, the group of Che showed that the hydrogen atom transfer (HAT) reaction can actually be used to generate the desired active radical species, thereby leading to product formation rather than deactivation. 21 However, all of the above-mentioned reactions require highenergy carbene precursors bearing excellent leaving groups to generate the reactive carbene radical intermediate (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In one notable study, de Bruin and Reek increased the turnover numbers (TONs) of cyclopropanations and intramolecular CH activations by confining a cobalt-porphyrin catalyst in a large nanocube ( 1 ) comprising six porphyrin walls bound together by eight (bipy) 3 Fe 2+ (bipy = 2,2′-bipyridine) vertices that are connected to the porphyrins via imine linkages (Scheme A) . These connections are dynamic enough to allow uptake of a [(4-pyridyl) 4 porphyrin]­Co II guest (TPyPCo II ), providing a way to isolate this catalyst inside the cube to stabilize radical-carbene ligands against detrimental radical dimerizations. , This example exclusively involves metal-bound radicals, in contrast to the fully organic radical intermediates generated by H atom abstraction or M–C homolysis. The ability of artificial porous materials to guide the reactivity of free alkyl radicals may, however, be responsible for the improved selectivity of C–H halogenations in a metal–organic framework reported by Li and Zhou, though we can only speculate since no mechanistic details were examined …”
Section: Introductionmentioning
confidence: 99%